UNIT 4.11 Genome Annotation and Curation Using MAKER and MAKER‐P. Issue 1 (12th December 2014) - Campbell, Michael S.; Holt, Carson; Moore, Barry; Yandell, Mark
Abstract : This unit describes how to use the genome annotation and curation tools MAKER and MAKER‐P to annotate protein‐coding and noncoding RNA genes in newly assembled genomes, update/combine legacy annotations in light of new evidence, add quality metrics to annotations from other pipelines, and map existing annotations to a new assembly. MAKER and MAKER‐P can rapidly annotate genomes of any size, and scale to match available computational resources. © 2014 by John Wiley & Sons, Inc.